A review on control strategies for compensation of hysteresis and creep on piezoelectric actuators based micro systems. (June 2020) - Sabarianand, D.V.; Karthikeyan, P.; Muthuramalingam, T.
Highlights: Prandtl-Ishlinskii hysteresis model can provide better performance. The feedback controller reduces the hysteresis non-linearity. Fuzzy logic controller can minimize the low amplitude vibration. Abstract: The piezoelectric actuators are widely used to realize high precise motion with fractional force and torque in both linear and rotary joints of the micro-systems. The control system plays a major role on overall dynamics including positioning and tracking objectives in piezoelectric actuator based micro-systems. The piezoelectric actuator inherently has its own non-linear behaviour such as hysteresis, creep, thermal drift and vibration which deteriorates overall performances including stability of the developed systems. This article reviews the various efforts for solving the major issues such as hysteresis and creep. It has been inferred that generalized control solution is not appropriate for all kind of piezoelectric actuators. Hence it has been observed that appropriate control strategies has to be implemented for reducing tracking error, position error and non-linear characteristic of piezoelectric actuator namely hysteresis and creep.